Health and fertility of ICSI-conceived young men: study protocol. Issue 4 (3rd October 2020) - Catford, S R; Lewis, S; Halliday, J; Kennedy, J; O'Bryan, M K; McBain, J; Amor, D J; Rombauts, L; Saffery, R; Hart, R J; McLachlan, R I
Abstract: STUDY QUESTIONS: What are the long-term health and reproductive outcomes for young men conceived using ICSI whose fathers had spermatogenic failure (STF)? Are there epigenetic consequences of ICSI conception? WHAT IS KNOWN ALREADY: Currently, little is known about the health of ICSI-conceived adults, and in particular the health and reproductive potential of ICSI-conceived men whose fathers had STF. Only one group to date has assessed semen parameters and reproductive hormones in ICSI-conceived men and suggested higher rates of impaired semen quality compared to spontaneously conceived (SC) peers. Metabolic parameters in this same cohort of men were mostly comparable. No study has yet evaluated other aspects of adult health. STUDY DESIGN, SIZE, DURATION: This cohort study aims to evaluate the general health and development (aim 1), fertility and metabolic parameters (aim 2) and epigenetic signatures (aim 3) of ICSI-conceived sons whose fathers had STF (ICSI study group). There are three age-matched control groups: ICSI-conceived sons whose fathers had obstructive azoospermia (OAZ) and who will be recruited in this study, as well as IVF sons and SC sons, recruited from other studies. Of 1112 ICSI parents including fathers with STF and OAZ, 78% (n = 867) of mothers and 74% (n = 823) of fathers were traced and contacted. Recruitment of ICSI sons started in March 2017 and will finish in July 2020. Based on preliminary participation rates, we estimate the following sample size will be achieved for the ICSI study group: mothers n = 275, fathers n = 225, sons n = 115. Per aim, the sample sizes of OAZ-ICSI (estimated), IVF and SC controls are: Aim 1—OAZ-ICSI: 28 (maternal surveys)/12 (son surveys), IVF: 352 (maternal surveys)/244 (son surveys), SC: 428 (maternal surveys)/255 (son surveys); Aim 2—OAZ-ICSI: 12, IVF: 72 (metabolic data), SC: 391 (metabolic data)/365 (reproductive data); Aim 3—OAZ-ICSI: 12, IVF: 71, SC: 292. PARTICIPANTS/MATERIALS, SETTING, METHODS: Eligible parents are those who underwent ICSI at one of two major infertility treatment centres in Victoria, Australia and gave birth to one or more males between January 1994 and January 2000. Eligible sons are those aged 18 years or older, whose fathers had STF or OAZ, and whose parents allow researchers to approach sons. IVF and SC controls are age-matched men derived from previous studies, some from the same source population. Participating ICSI parents and sons complete a questionnaire, the latter also undergoing a clinical assessment. Outcome measures include validated survey questions, physical examination (testicular volumes, BMI and resting blood pressure), reproductive hormones (testosterone, sex hormone-binding globulin, FSH, LH), serum metabolic parameters (fasting glucose, insulin, lipid profile, highly sensitive C-reactive protein) and semen analysis. For epigenetic and future genetic analyses, ICSI sons provide specimens of blood, saliva, sperm and seminal fluid while their parents provide a saliva sample. The primary outcomes of interest are the number of mother-reported hospitalisations of the son; son-reported quality of life; prevalence of moderate-severe oligozoospermia (sperm concentration <5 million/ml) and DNA methylation profile. For each outcome, differences between the ICSI study group and each control group will be investigated using multivariable linear and logistic regression for continuous and binary outcomes, respectively. Results will be presented as adjusted odds ratios and 95% CIs. STUDY FUNDING/COMPETING INTERESTS: This study is funded by an Australian National Health and Medical Research Council Partnership Grant (NHMRC APP1140706) and was partially funded by the Monash IVF Research and Education Foundation. L.R. is a minority shareholder and the Group Medical Director for Monash IVF Group, and reports personal fees from Monash IVF group and Ferring Australia, honoraria from Ferring Australia, and travel fees from Merck Serono, MSD and Guerbet; R.J.H. is the Medical Director of Fertility Specialists of Western Australia and has equity in Western IVF; R.I.M. is a consultant for and a shareholder of Monash IVF Group and S.R.C. reports personal fees from Besins Healthcare and non-financial support from Merck outside of the submitted work. The remaining authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: Not applicable. TRIAL REGISTRATION DATE: Not applicable. DATE OF FIRST PATIENT'S ENROLMENT: Not applicable.